2022
DOI: 10.1002/ibra.12018
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in the influence of lipid metabolism on cognitive impairment

Abstract: Cognitive impairment (CI) is a mental disorder related to cognition and understanding, which is mainly categorized into mild CI and senile dementia. This disease is associated with multiple factors, such as chronic brain injury, aging, chronic systemic disease, mental state, and psychological factors. However, the pathological mechanism of CI remains unclear; it is usually associated with such underlying diseases as diabetes and hyperlipidemia. It has been demonstrated that abundant lipid metabolism indexes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…In addition, among the 32 MitoDEGs involved in metabolism, 11 genes are implicated, including six in lipid metabolism (ACADL, THEM4, ACSM3, LYPLA1, TSPO, and SCP2), one in carbohydrate metabolism (HMGCL), one in amino acid metabolism (GLS2), and one in nucleotide metabolism (FHIT), ( Figure 8B ). Notably, it has been demonstrated that lipid metabolism disorders are closely related to cognitive function, as evidenced by the observation that knockout of a key enzyme in mitochondrial fatty acid oxidation causes cognitive impairment ( Zhang et al, 2022 ; Morant-Ferrando et al, 2023 ). Importantly, our findings shed light on the role of metabolism, especially lipid metabolism, in the cognitive impairment induced by SD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among the 32 MitoDEGs involved in metabolism, 11 genes are implicated, including six in lipid metabolism (ACADL, THEM4, ACSM3, LYPLA1, TSPO, and SCP2), one in carbohydrate metabolism (HMGCL), one in amino acid metabolism (GLS2), and one in nucleotide metabolism (FHIT), ( Figure 8B ). Notably, it has been demonstrated that lipid metabolism disorders are closely related to cognitive function, as evidenced by the observation that knockout of a key enzyme in mitochondrial fatty acid oxidation causes cognitive impairment ( Zhang et al, 2022 ; Morant-Ferrando et al, 2023 ). Importantly, our findings shed light on the role of metabolism, especially lipid metabolism, in the cognitive impairment induced by SD.…”
Section: Discussionmentioning
confidence: 99%